Development of a 14-degree of freedom prototype biped robot - Khaw, Aik Hau. (2008)
An autonomous, anthropomorphic and inexpensive biped robot named Proto2 has been built. It possesses 14 Degrees of Freedom and is actuated by positional servomotors. Four-bar and five-bar linkages are used for the power transmission of joints actuation of the biped robot and they are further discussed in the thesis.